PROBLEMAS POTENCIALMENTE SIGNIFICATIVOS PARA O ENSINO E APRENDIZAGEM DAS TEORIAS ÁCIDO-BASE DE BRÖNSTED-LOWRY E LEWIS - FAUSTINO, LARISSA DE LIMA (2023)
In Higher Education, in the first year of the Chemistry course, students have contact with the fundamental concepts of the field and its three levels of knowledge (macroscopic, microscopic, and symbolic) through the subject of General Chemistry. Commonly, students demonstrate difficulties in transitioning among these levels, while also reporting limited understanding of the scientific concepts or models, such as acid-base theories. Under the framework of David Ausubel's Theory of Meaningful Learning, reflection was made on the need to assist the student in the meaningful assimilation of content, so that the instructional material should also adhere to the same principle of being potentially meaningful. From this perspective, the aim of this study was to investigate the possibilities and implications of Potentially Meaningful Problems, referred to as PMPs, when applied to the Brönsted-Lowry and Lewis acid-base content in a General Chemistry course at the Higher Education level. In the format of problem situations or case studies, the PMPs encompassed attractive themes linked to everyday or professional situations in the field of Chemistry, aiming to encourage the integration of theory and practice and a better understanding of the microscopic and symbolic levels of the mentioned content. This was a qualitative research in which data were collected through bibliographic research, interviews with teachers, questionnaires, and the use of the PMPs with the students. The results indicated that, when it comes to the acid-base theory, students possess weak subsumers, do not satisfactorily develop explanations, and are unable to express the symbols of electronic movements between acidic and basic species. At the same time, there is evidence that PMPs can stimulate interaction, mediation, and investigation in the classroom, proving to be potential resources for instructors in undergraduate education.